GROUP COUNSELING USING THE SOLUTION-FOCUSED BRIEF COUNSELING APPROACH IN OVERCOMING STUDENTS' ACADEMIC PROBLEMS - Habsy, Bakhrudin All; Putri, Fira Alviana Rachelia; Damayanti, Shinta Anisa; Fajar, Tasha Haty (Jurnal Kajian Pendidikan dan Psikologi, 2025)
Group counseling is one of the effective methods in providing psychological support and problem solving for individuals experiencing various psychological challenges. One approach that has received widespread attention in the context of group counseling is the Solution-Focused Brief Counseling (SFBC) Approach.Solution Focused Brief Counseling is a counseling approach based on a postmodern approach which is also called constructive therapy, besides that this SFBC approach also focuses on discussing solutions provided or offered in the counseling process.This literature study aims to evaluate the effectiveness of group counseling using the SFBC approach in overcoming various psychological problems. The research method used is a literature study, by searching and analyzing various articles, books, and scientific journals related to group counseling and the SFBC approach. The Brief Solution Focused Counseling (SFBC) approach is an effective approach in helping individuals find solutions to psychological problems, especially when applied in a group setting. Nonetheless, the effectiveness of SFBC may vary depending on the specific characteristics and problems of the counselee.